Efektifitas Edukasi Tentang Jajanan Sehat Terhadap Peningkatan Pengetahuan dan Sikap Siswa Overweight: The Effectiveness of Healthy Snack Education on Improving Knowledge and Attitude of Overweight Students - Firnaliza Rizona; Karolin Adhisty; Fuji Rahmawati; Tri Candraca Firman (NERS Jurnal Keperawatan, 2019)
Overweight on children can result an obesity. Obesity on children have become a global problem which should be handled immediately. One of the precipitation of overweight is food intake that is unhealthy snacking. One of the method for increasing the number of knowledge and attitude about healtyh snack on school aged children is health education. Peer could influencing the children habit in consuming snacking, so that group discussion can give impact on health education process. This research aim was to know the efektivity of education through Focus group discussion (FGD) to overweight children’s knowledge and attitude about healthy snacking. This research was used approach of quasi experiment with one group pre-posttest design. The number of respondent was 50 overweight student divided become five group. Sample election used purposive sampling and FGD process conducted twice meeting. Data collected by using quessioner on pretest and posttest. Based on the result’s data, there were increasing mean number of knowledge from 14.78 become 17.00 and mean number of attitude from 11.72 become 13.22. The statistic result with Wilcoxon test showed that there were effectiveness of education with the differences of knowledge value and attitude value pre and post FGD with p value =0,000. Education concerning healthy snacking with group discussion can improve the value of knowledge and attitude school aged children with overweight for comprehending about healthy snacking. For school in order to inform about healthy snack on learning process with discussion which involve being active of children or by another media such as poster or leaflet.